Assessment of Symptom Severity, Urinary Flow, and Prostate Volume in Men with Benign Prostatic Hyperplasia: A Cross-Sectional Correlation Study: Urinary Flow and Prostate Volume in Men with Benign Prostatic Hyperplasia - Parekh, Anum Fatima; Rehmani, Madiha Saleem; Channa, Suhail Akhtar; Akhtar, .; Khan, Muhammad Zohaib Zafar; Mansoor, Muhammad (Pakistan Journal of Health Sciences, 2025)
Benign prostatic hyperplasia (BPH) is a common cause of lower urinary tract symptoms (LUTS) in ageing men, yet patient-reported symptoms, urinary flow parameters, and prostate size often show inconsistent clinical relationships. Clarifying how these measures relate may improve diagnostic interpretation and clinical decision-making. Objectives: To evaluate the correlations among symptom severity (IPSS), peak urinary flow rate (Qmax), and prostate volume in men with BPH. Methods: A cross-sectional analytical study was conducted among 56 men aged ≥50 years with clinically diagnosed BPH. Symptom severity was assessed using the International Prostate Symptom Score (IPSS). Uroflowmetry provided Qmax values, and transabdominal ultrasonography measured prostate volume. Pearson correlation coefficients with 95% confidence intervals were calculated to assess associations among variables. Results: The mean age of participants was 62.79 ± 6.64 years, and most reported moderate to severe symptoms (mean IPSS 21.79 ± 6.22). No significant correlation was found between IPSS and Qmax (r = –0.064, p = 0.639; 95% CI –0.32 to 0.20) or between IPSS and prostate volume (r = 0.216, p = 0.110; 95% CI –0.03 to 0.45). Prostate volume showed a weak, nonsignificant inverse association with Qmax (r = –0.139, p = 0.306; 95% CI –0.37 to 0.13). Conclusion: The absence of significant correlations among IPSS, Qmax, and prostate volume confirms that symptom burden, flow limitation, and gland size represent different dimensions of BPH. Clinical decision-making should therefore integrate these measures collectively rather than interpreting them in isolation